2013
DOI: 10.14260/jemds/1130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pregnancy Induced Hypertension on Human Placenta

Abstract: Placenta is a unique organ which arise de novo, directly related to the growth and development of the foetus in the uterus. A thorough examination of the placenta inutero, as well as post-partum, gives valuable information about the state of the foetal well being. Pregnancy Induced Hypertension is a well recognized obstetric hazard and observed more frequently in developing countries. OBJECTIVES: The present study was undertaken to analyze placental changes in the pregnancy induced hypertension. MATERIAL AND M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
(10 reference statements)
6
9
0
Order By: Relevance
“…A significant increase in syncytial knot formation in placental villi indicates the disturbance in the hormonal factors, which may probably lead to altered morphometry of placenta resulting in PIH in the mother. In the present study, stromal fibrosis was also increased in hypertensive group which corresponds with the study of Rohini Motwani et al 13 , Heazella AEP et al 18 , Kristina L et al 19 and…”
Section: 12supporting
confidence: 92%
See 3 more Smart Citations
“…A significant increase in syncytial knot formation in placental villi indicates the disturbance in the hormonal factors, which may probably lead to altered morphometry of placenta resulting in PIH in the mother. In the present study, stromal fibrosis was also increased in hypertensive group which corresponds with the study of Rohini Motwani et al 13 , Heazella AEP et al 18 , Kristina L et al 19 and…”
Section: 12supporting
confidence: 92%
“…15,16 Presence of syncytial knots increases with increasing gestational age, and with conditions of uteroplacental mal-perfusion and are important in placental examination. 17 In our study, increased syncytial knots in placenta were observed in 70% cases with severe hypertension whereas placenta of only 10% of normotensive mothers showed syncytial knots which was also reported by Rohini Motwani et al 13 , Heazella AEP et al 18 and Kristina L et al 19 They also hypothesized that the formation of syncytial knots may be induced by exposure to hypoxia. A significant increase in syncytial knot formation in placental villi indicates the disturbance in the hormonal factors, which may probably lead to altered morphometry of placenta resulting in PIH in the mother.…”
Section: 12supporting
confidence: 80%
See 2 more Smart Citations
“…In different studies, placental weight in hypertensive pregnancies has been reported to vary from 345.96 g to 524.24 g whereas that in normotensive pregnancies ranged from 435.92 g to 557.8 g. 12,13 The difference in placental weight of two groups in present study was 77.77 g. Extent of this difference has ranged widely in different studies. Qureshi et al found this difference to be 33 g only while Motwani et al found it as 67 g, similar to our study, Kulandaivelu et al in their study reported it to be 73 g, however, on a higher note Nag et al found this difference to be as high as 94 g and Salmani et al even surpassed this and reported this difference as 124 g. [13][14][15][16][17] The profile of differences in placental weight between hypertensive group and normotensive groups in different studies might be due to difference in different types of HDPs included in the assessment. Studies reporting a higher difference generally have a higher component of severe HDPs like severe preeclampsia and eclampsia as compared to gestational hypertension.…”
Section: Methodssupporting
confidence: 86%